2013
DOI: 10.1111/jnc.12464
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII represses transcriptionally active β‐catenin to mediate acute ethanol neurodegeneration and can phosphorylate β‐catenin

Abstract: Prenatal ethanol exposure causes persistent neurodevelopmental deficits by inducing apoptosis within neuronal progenitors including the neural crest. The cellular signaling events underlying this apoptosis are unclear. Using an established chick embryo model, we previously identified ethanol’s activation of CaMKII as a crucial early step in this pathway. Here we report that CaMKII is pro-apoptotic because it mediates the loss of transcriptionally active β-catenin, which normally provides trophic support to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…The W98S/D lines were selected for characteristics independent of ethanol response and, in the absence of genetic lineage groups, many of their gene differences are unlikely to affect ethanol responses. However, several of these significantly altered genes encode proteins that directly participate in or modify the calcium-CaMKII-β-catenin pathway that governs the ethanol-induced apoptosis studied here (Garic et al 2011; Flentke et al 2011, 2013). Thus, they are good candidates to shape cellular responses to ethanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The W98S/D lines were selected for characteristics independent of ethanol response and, in the absence of genetic lineage groups, many of their gene differences are unlikely to affect ethanol responses. However, several of these significantly altered genes encode proteins that directly participate in or modify the calcium-CaMKII-β-catenin pathway that governs the ethanol-induced apoptosis studied here (Garic et al 2011; Flentke et al 2011, 2013). Thus, they are good candidates to shape cellular responses to ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…In the well-characterized ethanol-sensitive line, Hy-Line W98S, ethanol (EC 50 = 52 mM) elicits an intracellular calcium transient that originates from a G protein-coupled receptor and phosphoinoside signaling. This calcium signal mediates the CaMKII-dependent destabilization of transcriptionally active β-catenin, a trophic factor for neural crest progenitors (Flentke et al 2011, 2013; Garic et al 2011; Garic-Stankovic et al 2005; Debelak-Kragtorp et al 2003). In contrast, ethanol-mediated events including calcium mobilization, apoptosis, and facial dysmorphology are significantly attenuated in ethanol-resistant strains such as DeKalb Black and Hy-Line W98D despite equivalent ethanol exposure (Debelak, et al 2000; Su et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ellies et al (2000) previously showed that the programmed cell death within a subset of neural crest progenitors depends on a non-canonical Wnt effector, and, following this lead, Flentke et al (2011) found that alcohol destabilizes β-catenin and its Wnt-dependent transcriptional activity within neural crest cells. The β-catenin destabilization is calcium-dependent and mediated not by known Wnt effectors including GSK3β and calpain, but rather by CaMKII (Flentke et al 2014). They went on to identify three previously-unrecognized CaMKII phosphorylation sites within β-catenin that target the protein for proteolytic destruction.…”
Section: Mechanistic Insights From Avian Models Of Fasdmentioning
confidence: 99%
“…Twenty hours after alcohol exposure, apoptotic neural crest cells (arrows) are observed as visualized by double-staining for the neural crest marker Sox 9 (green) and LysoTracker Red (red), which we showed previously detects TUNEL+ cells in this model. Adapted from Smith et al 2014. m, mesendoderm, nc, neural crest; nf, neural folds.…”
Section: Figurementioning
confidence: 99%
“…NFAT has been found to compete with -catenin to interact with Dsh and thus, negatively regulates -catenin dependent canonical Wnt signalling 48 . Several other components of Wnt/calcium pathway like CamkII and PKC, have also been reported to be involved in inhibiting canonical Wnt signalling possibly by targeting -catenin 40,[49][50][51] , thus indicating a crosstalk between canonical and Wnt/calcium noncanonical signalling.…”
Section: Non-canonical Wnt Signallingmentioning
confidence: 99%